2019
DOI: 10.1002/ecy.2726
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation‐independent niche differentiation and relative non‐linearity drive coexistence in a species‐rich grassland

Abstract: Citation: Zepeda, V., and C. Martorell. 2019. Fluctuation-independent niche differentiation and relative non-linearity drive coexistence in a species-rich grassland. Ecology 100(8):Abstract. Despite the advances in ecological theory, evidence for the relative importance of the different mechanisms that promote species coexistence is lacking. Some mechanisms depend on the presence of interannual fluctuations in the environment combined with interspecific differences in the responses to such fluctuations. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 41 publications
(122 reference statements)
0
57
0
Order By: Relevance
“…Empirical evidence supports both relative non‐linearity and the storage effect as coexistence mechanisms operating in nature, albeit mostly for plants and plankton (Adler et al ; Angert et al ; Caceres ; Chesson et al ; Descamps‐Julien &Gonzalez ; Zepeda & Martorell ). Relative non‐linearity could contribute most strongly to coexistence in species that diverge in life‐history traits (e.g.…”
Section: Coexistence In Fluctuating Environmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Empirical evidence supports both relative non‐linearity and the storage effect as coexistence mechanisms operating in nature, albeit mostly for plants and plankton (Adler et al ; Angert et al ; Caceres ; Chesson et al ; Descamps‐Julien &Gonzalez ; Zepeda & Martorell ). Relative non‐linearity could contribute most strongly to coexistence in species that diverge in life‐history traits (e.g.…”
Section: Coexistence In Fluctuating Environmentsmentioning
confidence: 98%
“…Recent theoretical and empirical studies have also concluded that species diverge along multiple niche axes, and that multiple coexistence mechanisms likely operate simultaneously to sustain nature’s diversity (Chesson et al ; Chesson , ; Ellner et al ; Zepeda & Martorell ). Using different resources and using the same resource at different times would both be expected to stabilise coexistence for the same reason: both dampen the strength of interspecific relative to intraspecific competition (Chesson ; Chesson & Huntely 1997; Chesson ).…”
Section: A Case For Multiple Coexistence Mechanismsmentioning
confidence: 99%
“…Niche partitioning in time, just as in resource partitioning in space, weakens the strength of inter-specific competition (vs. intra-specific competition) and allows an inferior competitor or low-density species to coexist with a superior competitor. Empirical evidence supports both relative non-linearity and the storage effect as coexistence mechanisms operating in nature, albeit mostly for plants and plankton (Adler et al 2006;Angert et al 2011;Caceres 1997;Chesson et al 2012;Descamps-Julien &Gonzalez 2005;Zepeda & Martorell 2019). Relative non-linearity could contribute most strongly to coexistence in species that diverge in life-history traits (e.g., fast vs. slow strategies) but otherwise have high niche overlap (Xiao & Fussmann 2013).…”
Section: Stabilizing Mechanismsmentioning
confidence: 98%
“…Recent theoretical and empirical studies have also concluded that species diverge along multiple niche axes, and that multiple coexistence mechanisms likely operate simultaneously to sustain nature's diversity (Chesson et al 2012;Chesson 2018Chesson , 2019Ellner et al 2016;Zepeda & Martorell 2019). Using different resources and using the same resource at different times would both be expected to stabilize coexistence for the same reason: both dampen the strength of interspecific relative to intra-specific competition (Chesson 2000;Chesson & Huntely 1997;Chesson 1985).…”
Section: A Case For Multiple Coexistence Mechanismsmentioning
confidence: 99%
“…235 received considerably less attention than the contribution of nonadditive responses (mainly 237 the storage effect). Nonlinear responses to coexistence were initially thought to be more 238 limited than for the latter (Chesson 1994), although recent studies suggest otherwise (Letten 239 et al 2018;Hallett et al 2019;Zepeda & Martorell 2019). Importantly, the contribution of 240 nonlinear responses to coexistence was thought to be limited to competition (e.g., (Chesson 241 1994(Chesson 241 , 2000) until very recently (Ellner et al 2019).…”
mentioning
confidence: 99%